Comparative pharmacokinetics of imepitoin after oral and rectal administration in healthy dogs. (May 2020) - Martlé, Valentine; Devreese, Mathias; Rauch, Saskia; Van Ham, Luc; Croubels, Siska; Vanhoorne, Valérie; Vervaet, Chris; Bhatti, Sofie
Highlights: Plasma concentrations of imepitoin were lower after rectal than oral administration. Time to maximal concentration did not differ significantly between administration routes. This study does not support rectal administration of imepitoin in dogs. Abstract: The purpose of the present study was to investigate if rectal administration of imepitoin in healthy dogs leads to plasma concentrations comparable to those after oral administration. Significantly lower systemic exposure and maximal plasma concentration ( C max ) of imepitoin was achieved after rectal compared to oral administration ( P  ≤ 0.001). Therefore, this study does not support the rectal administration of imepitoin in dogs.